Recent advances in copper-catalysed radical-involved asymmetric 1,2-difunctionalization of alkenes - Li, Zhong-Liang; Fang, Gui-Chun; Gu, Qiang-Shuai; Liu, Xin-Yuan (Chemical Society reviews, 2020)
The radical-involved 1,2-difunctionalization of alkenes has developed into a robust tool for preparation of complex organic molecules. Despite significant advances in this area, the catalytic asymmetric version still remains a challenging task mainly due to the difficulty in the stereocontrol of the highly reactive radical intermediates. Recently, owing to the good single-electron transfer ability and coordination with chiral ligands of copper catalysts, remarkable achievements in radical-involved asymmetric alkene difunctionalization have been made via synergistic combination of copper and chiral ligands. This tutorial review highlights the recent progress in copper-catalysed radical-involved asymmetric 1,2-difunctionalization of alkenes and the mechanistic scenarios governing the stereocontrol, with an emphasis on utilization of chiral ligands. This tutorial review highlights the recent progress in copper-catalysed radical asymmetric 1,2-difunctionalization of alkenes.